Generation of Non‐Classical Light Using Semiconductor Quantum Dots. Issue 1 (26th December 2019) - Trivedi, Rahul; Fischer, Kevin A.; Vučković, Jelena; Müller, Kai
Abstract: Sources of non‐classical light are of paramount importance for future applications in quantum science and technology such as quantum communication, quantum computation and simulation, quantum sensing, and quantum metrology. This Review is focused on the fundamentals and recent progress in the generation of single photons, entangled photon pairs, and photonic cluster states using semiconductor quantum dots. Specific fundamentals which are discussed are a detailed quantum description of light, properties of semiconductor quantum dots, and light–matter interactions. This includes a framework for the dynamic modeling of non‐classical light generation and two‐photon interference. Recent progress is discussed in the generation of non‐classical light for off‐chip applications as well as implementations for scalable on‐chip integration. Abstract : Sources of non‐classical light are of paramount importance for future applications in quantum science and technology. This Review addresses the generation of non‐classical light using semiconductor quantum dots. In addition to a comprehensive description of the underlying fundamentals, recent progress in the generation of single photons, entangled photon pairs, and photonic cluster states is discussed.